Situation Awareness Measurement in Remotely Controlled Cars - Linkov, Václav; Vanžura, Marek (Frontiers in Psychology, 2021)
This text provides a review of the current information concerning the measurement of the situation awareness (SA) of the teleoperators of remotely controlled cars. The teleoperators who drive these cars are in a remote location, and they control the cars through a communication interface. When measuring SA on a closed circuit without real traffic, the use of objective methods with probes is beneficial. Questions specifically should address the information provided on the road by haptic sensation, such as the slope of the road and the speed of the vehicle. Methods for measuring SA that involve probes and interruptions obviously are not suitable for use on public roads. A stable environment for the display and control of the communication interface allows the use of an eye tracker for measuring SA, and these features also facilitate the use of subjective observer-rating methods. Both of these methods have limitations, but they are suitable for driving on real roads because they are not intrusive. SA research in a real-road environment also should include a study concerning how the SA of other drivers is affected by seeing a car without a driver. Given the remote character of driving, cultural differences in cognition also may have significant influence on the SA of the teleoperator.